El Mercado Público de Barranquilla (1870-1930): De la historia de un edificio a una triangulación comercial - Jessille López García; Eduardo Gómez-Araujo; Roberto González Arana (Caravelle)
The article exposes the environment, the commercial and supply dynamics of the public market of Barranquilla between 1870 and 1930. In addition, the local socio-spatial concept of Triangulación comercial is proposed and developed, which seeks to explain the articulation of an environment made up of different physical spaces and close, but together they formed an intense commercial dynamic. Although, it did not conceive completely modern ideals, it allowed endowing this population with a synergic commercial framework that conveniently resolved commercialization and attended to the collection of taxes.